Avoiding Questionable Research Practices in Applied Psychology 2022
DOI: 10.1007/978-3-031-04968-2_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Improving Robustness of Psychological Research Findings in Four Steps

Abstract: This chapter is accepted for publication, but still needs to undergo copy-editing. Cite as: Nuijten, M. B. (accepted chapter). Assessing and improving robustness of psychological research findings in four steps. In W. O'Donohue, A. Masuda, and S. Lilienfeld (Eds.), Clinical psychology and questionable research practices. Springer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…Replication can increase practitioners' confidence in applying findings when providing evidence-based treatment, with particular relevance to 'clinical decision-making' (Palmer et al, 2021, p. 361). In response to calls for more replications (e.g., Nuijten, 2022), we conducted a replication of Jankowski et al's (2019) naturalistic study on the effectiveness of long-term psychodynamic psychotherapy. Jankowski et al found subgroups of responders, clients for whom depression and anxiety symptoms reduced and life satisfaction and social functioning improved.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Replication can increase practitioners' confidence in applying findings when providing evidence-based treatment, with particular relevance to 'clinical decision-making' (Palmer et al, 2021, p. 361). In response to calls for more replications (e.g., Nuijten, 2022), we conducted a replication of Jankowski et al's (2019) naturalistic study on the effectiveness of long-term psychodynamic psychotherapy. Jankowski et al found subgroups of responders, clients for whom depression and anxiety symptoms reduced and life satisfaction and social functioning improved.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a robustness check, our intent was to verify results 'through reanalysis before replicating a study in a new [independent] sample' (Nuijten, 2022, p. 381), and consistent with constructive replication, we examined whether findings were 'due to specific boundary conditions inherent to the original study' (Hüffmeier et al, 2016, p. 86). Furthermore, our application of three alternative analytic strategies to examine their influence on the substantive interpretations offered by Jankowski et al (2019) is a form of conceptual replication (Crandall & Sherman, 2016;Nuijten, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations